Gas-solid fluidized bed simulations using the filtered approach: Validation against pilot-scale experiments. (18th May 2020) - Yu, Wenchao; Fede, Pascal; Yazdanpanah, Mahdi; Amblard, Benjamin; Euzenat, Florian; Simonin, Olivier
Graphical abstract: Highlights: The large-scale fluidized bed simulations are validated against PSRI experiments. A SGS drag model based on the filtered approach is used without any specific tuning. Gas-solid flows inside the fluidized bed with different gas velocities are characterized. Validation in this study is a critical step toward industrial-scale fluidized bed simulations. Abstract: Numerical simulations of large-scale fluidized beds still remain challenging due to the computational limitation and experimental validation. In the present work, a CFD study of a large-scale fluidized bed is investigated using the NEPTUNE_CFD code based on an Eulerian n-fluid modeling approach. A SubGrid Scale (SGS) drag model based on the filtered approach is used to take into account the effect of very small solid structures unresolved with the coarse mesh. The numerical results are compared with the experimental data carried out in a pilot-scale cold-flow fluidized bed unit and provided by Particulate Solid Research Inc (PSRI). By applying the SGS drag model without any specific or empirical tuning, reasonably good grid-independence is achieved. The flow regimes inside the fluidized bed are well predicted for all the superficial gas velocities studied here. The bed density profiles and the solid entrainment fluxes are also in good agreement with the experimental measurement.